Antiproliferative and Antibacterial Activities of Cirsium scabrum from Tunisia. (12th July 2017) - Sahli, Ramla; Rivière, Céline; Dufloer, Cédric; Beaufay, Claire; Neut, Christel; Bero, Joanne; Hennebelle, Thierry; Roumy, Vincent; Ksouri, Riadh; Quetin-Leclercq, Joelle; Sahpaz, Sevser
Abstract : Several Cirsium species are known for their uses in traditional medicine and consequently are studied for their phytochemical content and their biological activities. In the framework of a previous study conducted on eight extremophile plants from Tunisia, we highlighted that the crude methanolic extract of C. scabrum, a not investigated thistle, showed moderate but quite selective cytotoxic activity against the cancerous cell line J774 compared to the noncancerous cell line WI38 (IC50 = 11.53  μ g/ml on J774, IC50 = 29.89  µ g/ml on WI38, and selectivity index = 2.6). In the current study, the partitions of the leaves of C. scabrum were analyzed for their antiproliferative activity on the same cell lines. From the most active petroleum ether partition, we isolated four triterpenoids including lupeol, taraxasterol acetate, and a (1 : 1) mixture of 25-hydroperoxycycloart-23-en-3 β -ol and 24-hydroperoxycycloart-25-en-3 β -ol. These two cycloartane-type triterpenoids are mostly responsible for this cytotoxic activity. On the other hand, the antimicrobial potential of this plant was also evaluated against 36 microorganisms. The moderate antibacterial activity against 6 Staphylococcus aureus and 2 Dermabacter hominis strains is mainly attributed to the butanol partition whose major compounds are glycosides of flavones.